"Writing for Publication" Language Enhancement Course as an Instrument of Developing Scientific Writing Skills of University Faculty and Staff; INTED2015 Proceedings - Goryanova L. N. Lyubov Nikolaevna (2015, 2015)
In the present world of global competitiveness and international collaboration, it has become essential for university academic staff and employees engaged in research to share results of their scientific work with the international community of science and education. One of the ways to enhance this global communication is through publication in the world-leading academic journals. Thus, in Russian National Research Universities, in accordance with their Strategic programme of development, having such publications has become part of criteria for measuring performance of research and teaching staff. However, for a vast majority of university employees, academic and scientific writing appears a highly challenging task due to the necessity to write in a foreign language, particularly English as the language of international importance. In the given situation, successful academic writing requires not only language proficiency but also proficiency in writing skills. The aim of this article is to share National Research Tomsk Polytechnic University (TPU) best practice in helping its employees gain the necessary skills by launching a professional language enhancement course "Writing for Publication". Special pedagogical conditions of the realisation of this programme are described. Among them are the following: the course structure and content, delivery and teaching principles and procedures, a native speaker as the main course instructor. It is believed that such an approach can help significantly TPU faculty and staff raise their international scientific writing activity, and, consequently, meet the new challenges and requirements of a global workplace. In addition, it is suggested that TPU experience can be successfully adopted by other universities in order to help their academic staff gain high-level professionally-oriented language competence for scientific purposes.